Adherence to the oral contraceptive pill: the roles of health literacy and knowledge - Liddelow, Caitlin; Mullan, Barbara; Boyes, Mark (2020)
Objective: The oral contraceptive pill is the most widely used method of contraception and when adhered to perfectly is 99% effective at preventing pregnancy. However, adherence to the pill is relatively low. Knowledge has shown to be important in continuation of the pill, and previous research shows the importance of health literacy in adhering to medication in chronic illnesses, but its role has yet to be explored in this behavior. Methods: This cross-sectional study examined the associations between health literacy, knowledge of the pill and adherence, as well as the predictive ability of these two variables and their interaction, in predicting adherence. Recruited through CloudResearch, 193 women (M age = 32.63 years, SD = 5.98) residing in the United States completed the Health Literacy Skills Instrument–Short Form, a previously validated measure of oral contraceptive pill knowledge and the Medication Adherence Report Scale. Results: Results showed a strong positive correlation between health literacy and adherence (r =.76) and moderate associations between health literacy and knowledge (r =.42), and knowledge and adherence (r =.42). The final model of the hierarchical multiple regression accounted for 59.8% of variance in adherence, with health literacy (β =.69) and length of time taking the pill (β =.13) the only significant predictors of adherence. Conclusion: Family planning clinics should consider assessing the patient’s health literacy skills before prescribing the pill to ensure patients fully understand the requirements.